2013
DOI: 10.4097/kjae.2013.65.6.574
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of a patient with undiagnosed paraganglioma -a case report-

Abstract: Retroperitoneal paragangliomas are uncommon neuroendocrine tumors which are derived from extra-adrenal paraganglioma with various clinical signs and symptoms. Although most extra-adrenal paragangliomas are histologically benign, some tumors can synthesize and secrete excess catecholamine from the tumor. Excessive production of catecholamine causes numerous cardiovascular manifestations such as severe hypertension, cardiomyopathy, cardiac arrhythmias, and even multiorgan failure. It can lead to high risks of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The anesthetic management of the surgical excision of the tumor requires the knowledge of physiological and pathological effects of catecholamine secreting tumors under the influence of anesthesia and surgery as they have a significant effect on the outcome of the surgery [13]. Excessive catecholamine production and secretion in the circulation poses serious lifethreatening cardiovascular complications like hypertension, myocardial infarction, pulmonary edema, arrhythmias, and cardiomyopathy [14]. The major anesthetic concerns include adequate preoperative optimization of the blood pressure, safe conduct of anesthesia, smooth intubation and extubation attenuating the stress response, maintaining hemodynamic stability, supplementation of steroids, monitoring glycaemic status and providing balanced multimodal analgesia [15].…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic management of the surgical excision of the tumor requires the knowledge of physiological and pathological effects of catecholamine secreting tumors under the influence of anesthesia and surgery as they have a significant effect on the outcome of the surgery [13]. Excessive catecholamine production and secretion in the circulation poses serious lifethreatening cardiovascular complications like hypertension, myocardial infarction, pulmonary edema, arrhythmias, and cardiomyopathy [14]. The major anesthetic concerns include adequate preoperative optimization of the blood pressure, safe conduct of anesthesia, smooth intubation and extubation attenuating the stress response, maintaining hemodynamic stability, supplementation of steroids, monitoring glycaemic status and providing balanced multimodal analgesia [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be due to the sudden release of excess catecholamine contained in paraganglioma, which is mistaken for GIST. Most report considerable hemodynamic stability during induction and maintenance of anesthesia using inhalation anesthesia and opioids, but experience a hypertensive crisis at the moment the mass is maneuvered [7,10]. In a case described in 2009, Lowenthal et al [6] reported that the tumor located near the stomach was mistaken for GIST, but they experienced a hypertensive crisis as soon as the initial operational step for tumor removal was performed for resection.…”
Section: Abdominal Computed Tomography Image Revealed a 39脳63mentioning
confidence: 99%